ESG AND TECHNOLOGY USE IN SMES: A FUTURE APPROACH TO GREEN INNOVATION - Sugiantari, Ida Ayu Putu Ayunda Aprilia (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
This study explains how green innovation and using new technology can help small and medium-sized businesses (SMEs) become more sustainable. As customers and government agencies push for more eco-friendly practices, SMEs are dealing with both difficulties and chances when it comes to adopting sustainable technologies. The research points out main challenges like expensive start-up costs and a lack of technical knowledge, but it also shows the long-term advantages, such as saving money and becoming more competitive. The paper uses a detailed review of existing research to find ways to overcome these challenges, stressing the need to include green technologies in how businesses operate. It also suggests that government help, like financial support and training programs, is important for creating an environment that encourages sustainable innovation. The study ends by saying that by using green innovation, SMEs can meet environmental rules and stand out in the market, which helps achieve bigger sustainability goals worldwide.